A new method to simulate permeability degradation of stressed concrete. (20th June 2018) - Wimalasiri, Manuka; Robert, D.J.; Li, Chun-Qing; Baji, Hassan
Highlights: A methodology to determine the permeability degradation of stressed concrete. Easy to determine permeability with different mechanical properties and geometries. Permeability starts to degrade when stress reaches a certain threshold value. Aggregate fraction is the most influential factor for permeability degradation. Aggregates with sharper edges tend to result higher permeability values for concrete. Abstract: Concrete permeability is usually determined by testing unstressed, non-damaged specimens in laboratories as a constant. In reality, however, concrete is subjected to various operational loads in the time span of its service life. Therefore, the permeability of stressed concrete can be time-variant and completely different from that of unstressed conditions. This paper intends to develop a new methodology to determine the permeability of stressed concrete over time, based on the damage mechanics of concrete meso-structure in conjunction with Monte Carlo simulation and finite element analysis. It is found in this study that the permeability of concrete starts to increase when the applied stress in concrete reaches a certain threshold value for the given aggregate fraction. It is also found that the aggregate fraction is the most influential factor for permeability degradation of concrete. The significance of the developed methodology is that it can determine the permeability degradation of concrete with different mechanical properties and geometries of constituent materials under various applied loads over time, which would be otherwise impractical experimentally.